Chromatographic evaluation and antimicrobial activity of Neem (Azadirachta indica A. Juss., Meliaceae) leaves hydroalcoholic extracts - Alves,Priscila D. (2009)
Neem (Azadirachta indica) is an Indian tree well known for its several pharmacological activities, including antimicrobial activity. More than 300 composites have already been isolated and azadirachtin (AZA) is its main active component. In the present work, Neem leaves hydroalcoholic extracts were prepared by percolation in 96% ethanol different concentrations (50%, 60%, 70%, 80% and 90% (v/v)). The presence of AZA was tested by TLC by eluting the extracts and a standard solution of AZA through a chromatographic plate developed with anisaldehyde/sulfuric acid solution followed by heating. By HPLC, extracts elution took place on a C18 column, water:acetonitrile (60:40) as mobile phase, 1.0 mL/min flow rate and detection at λ217 nm. The extracts did not display AZA spots or peaks, however, they were tested against Gram-positive and Gram-negative bacteria, yeasts and a mold fungus. The extracts were tested in different increasing concentrations, in order to detect a dose-dependent relationship of the activity. Despite the absence of AZA, the 70% and 80% (v/v) ethanol extracts showed activity against Staphylococcus aureus. However, this activity was not dose-dependent according to Tukey's test (q0,05;3;7).